MONETAR POLICY, MACROECONOMIC VARIABLES AND THE PERFORMANCE OF ISLAMIC BANKS FINANCING - Khalidin, Bismi (Archives of Business Research, 2022)
Islamic banks are banks that operate based on sharia, where one of the principles is free from usury or interest rates. Instead of the rates, the banks uses a profit sharing system. In Indonesia, the Islamic banks grow significantly, even though the prevailing monetary policy is still based on the interest system. This phenomenon is interesting to study, because on the one hand there is a close relationship between banking and monetary policy, but on the other hand monetary policy is based on interest rates while the Islamic banks are based on profit sharing rates. This study aims to examine the relationship and influence of monetary policy and macroeconomic variables on the performance of the Islamic bank financing. This research was conducted from 2010 to 2019, by using statistical approaches of Vector Auto Regression (VAR) and Pearson Correlation. The results show that the performance of Islamic bank financing, both profit-sharing-based and murabahah financings, is influenced by monetary policy and several selected macroeconomic variables. In addition, the profit sharing rates of financing is influenced by conventional bank interest rates and the rates of some monetary instruments. One important thing in this finding is that the financing and the profit sharing rate applied by Islamic banks resemble those of conventional banks, so that the influence of interest rates is very dominant in the operations of Islamic banks, both from monetary policy instruments and other interest rates.